The CRTh2 polymorphism rs533116 G > A associates with asthma severity in older females - Shrestha Palikhe, Nami; Mackenzie, Constance A.; Licskai, Christopher; Kim, Richard B.; Vliagoftis, Harissios; Cameron, Lisa (Frontiers in Medicine, 2022)
CRTh2 is G protein coupled receptor for prostaglandin D2 (PGD)2 expressed by immune cells that drive type 2 inflammation such as CD4+ T cells (Th2), eosinophils and group 2 innate lymphoid cells (ILC2) as well as structural cells including smooth muscle and epithelium. CRTh2-expressing cells are increased in the blood and airways of asthmatics and severe asthma is characterized by increased activity of the PGD2-CRTh2 pathway. The CRTh2 single nucleotide polymorphism (SNP) rs533116 G>A is associated with development of asthma and increased Th2 cell differentiation. To examine whether CRTh2 rs533116G>A associates with asthma severity. Since severe asthma is more common in females than males, we performed a sex-stratified analysis. Clinical data from asthmatics (n=170) were obtained from clinic visits and chart review. Asthma severity was assessed according to ERS/ATS guidelines. Peripheral blood cells were characterized by flow cytometry and qRT-PCR. Genotyping was performed by TaqMan assay. Results Older females (≥ 45 years) homozygous for minor A allele of rs533116 were more likely to have severe asthma, lower FEV1, a higher prescribed dose of inhaled corticosteroid and more type 2 inflammation than females carrying GA or GG genotypes. Comparing females and males with the AA genotype also revealed that women had more type 2 inflammation. The polymorphism CRTh2 rs533116 G>A associates with severe asthma and type 2 inflammation in older females. This study reveals a gene-sex-aging interaction influencing the effect of CRTh2 on asthma severity.